Testing of an inexpensive modified atmosphere chamber for small farmers using soaked grain as oxygen scavenger - Bartosik, Ricardo Enrique; Cardoso, Marcelo Leandro; De La Torre, Diego; Abadia, María Bernadette; Tulli, María Celia; Taher, Hernán Ignacio; Maciel, Gisele (University of Manitoba, Canadá, 2021)
Insects are one of the major causes of grain losses. Fumigation methods or controlled atmosphere (CA) treatments usually require sophisticated technologies that are not affordable in subsistence farming. This study focused in testing an inexpensive and effective modified atmosphere (MA) chamber using standard liners and soaked grain as O2 scavenger. Freshly harvested wheat (14% m.c.) was bagged in 35 kg plastic raffia bags (non-hermetic). A stack of 13 bags was assembled inside a polyethylene liner of 70-micron thickness and dimensions of 1.0 m x 1.0 m x 1.8 m. The liner was closed by twisting, folding, and tying the opening with a rope. The airtightness was tested by a pressure decay test (PDT). Four treatments were evaluated, including a control (only dry grain) and three treatments with soaked grain as oxygen scavenger. Oxygen and CO2 concentrations were measured with a portable gas analyzer. Results indicated that the respiration rate of soaked grain was 120 to 150 times greater that that of dry wheat. The incorporation of a small quantity of soaked grain as oxygen scavenger (1% dry matter) resulted in a reduction of the oxygen concentration to less than 2%, creating a lethal atmosphere for insects. The PDTs of the chambers were from 0.15 to more than 19 min. The variability in the final O2 and CO2 concentration achieved in all the treatments was quite low in spite of the variability of the PDT. This would suggest that the effect of incorporating oxygen scavengers was of a much larger magnitude than the differences in airtightness observed. This study demonstrated that an effective MA chamber can be created using standard 70-micron polyethylene liner, a simple sealing method and sacrificing only small portion of soaked grain as oxygen scavenger